Postcolonialism and Indonesian Maritime Diplomacy: Reinterpreting the Ambalat Dispute Toward Institutional Reform and Regional Solidarity in Southeast Asia - Maulana, Muhammad Alfian (Papua Journal of Diplomacy and International Relations, 2026)
This study examines Indonesia’s diplomatic strategy in the Ambalat maritime dispute with Malaysia under the post-2024 Prabowo administration. Using Postcolonial International Relations theory and Le Mière’s Cooperative Maritime Diplomacy framework, it analyzes how colonial legacies are reframed as strategic resources. Through critical discourse analysis of speeches, bilateral statements, and ASEAN engagements (October 2024–2025), the study identifies three dimensions. First, the narrative dimension repositions Malaysia as a shared inheritor of colonial borders rather than an adversary. Second, the practical dimension institutionalizes this narrative through joint development mechanisms separating resource management from sovereignty disputes. Third, the institutional dimension expands this approach into ASEAN maritime governance discourse. The study argues that postcolonial identity operates as active diplomatic agency, conceptualized as postcolonial maritime diplomacy. KEYWORDSIndonesian Maritime Diplomacy; Institutional Reform; Postcolonialism; Regional Cooperation